Effect of movement velocity on the relationship between training load and the number of repetitions of bench press - Sakamoto, A.; Sinclair, P. J. (The Journal of Strength and Conditioning Research, 2006)
This study investigated the effect of movement velocity on the relationship between loading intensity and the number of repetitions of bench press. Thirteen healthy men (age = 21.7 ± 1.0 years; weight = 76.8 ± 2.5 kg; 1 repetition maximum [1RM] = 99.5 ± 6.0 kg), who were involved in regular weight training, voluntarily participated in the experiment. Subjects performed bench presses on a Smith machine at 5 different intensities (40-80% 1RM), repeated for 4 velocity conditions (slow: 0.15 ± 0.03 m·s-1; medium: 0.32 ± 0.07 m·s-1; fast: 0.52 ± 0.12 m·s-1; ballistic: maximum velocity), which were randomly assigned over 5 experimental sessions after a 1RM test. Velocity significantly changed the relationship between intensity (%1RM) and the number of reps performed (p < 0.001), with faster velocities producing a higher number of reps. A significant interaction between intensity and velocity meant that velocity had a much greater effect on repetitions at lower intensities. These results suggest that the benefits of using a stretch-shortening cycle during faster movements outweigh the associated disadvantages from the force-velocity relationship. The practical applications of this study are that, when trainees are assigned a resistance training with specific RM values, the lifted intensity (%1RM) or weights will not be consistent unless velocity is controlled during training.